Principal’s Leadership Management Strategy in Increasing the Quality of Educators’ Performance - Fatimah, Netty; Ahyani, Nur; Destiniar, Destiniar (PPSDP International Journal of Education, 2023)
The primary determinant of the educational process at SMP Negeri 1 Kayuagung is the leadership of the principal. Through resource performance personnel, primarily instructors, leaders shape students. This study’s goal was to use qualitative descriptive methods and naturalistic observation to examine the principal’s leadership strategy for raising teacher performance standards. Both secondary and primary data are used as the sources for this study. As a result, to generate the best students, educational resources must be sufficiently superior, making it important for the principal to boost the caliber of educator performance.